Renal involvement in eosinophilic granulomatosis with polyangiitis (EGPA): a multicentric retrospective study of 63 biopsy-proven cases. (28th August 2020) - Durel, Cécile-Audrey; Sinico, Renato A; Teixeira, Vitor; Jayne, David; Belenfant, Xavier; Marchand-Adam, Sylvain; Pugnet, Gregory; Gaultier, Jacques; Le Gallou, Thomas; Titeca-Beauport, Dimitri; Agard, Christian; Barbet, Christelle; et al.
Abstract: Objective: Eosinophilic granulomatosis with polyangiitis (EGPA) is a systemic small-vessel vasculitis characterized by asthma, hypereosinophilia and ANCA positivity in 40% of patients. Renal involvement is rare and poorly described, leading to this renal biopsy-proven based study in a large EGPA cohort. Methods: We conducted a retrospective multicentre study including patients fulfilling the 1990 ACR criteria and/or the 2012 revised Chapel Hill Consensus Conference criteria for EGPA and/or the modified criteria of the MIRRA trial, with biopsy-proven nephropathy. Results: Sixty-three patients [27 women, median age 60 years (18–83)] were included. Renal disease was present at vasculitis diagnosis in 54 patients (86%). ANCA were positive in 53 cases (84%) with anti-MPO specificity in 44 (83%). All patients had late-onset asthma. Peripheral neuropathy was present in 29 cases (46%), alveolar haemorrhage in 10 (16%). The most common renal presentation was acute renal failure (75%). Renal biopsy revealed pauci-immune necrotizing GN in 49 cases (78%). Membranous nephropathy (10%) and membranoproliferative GN (3%) were mostly observed in ANCA-negative patients. Pure acute interstitial nephritis was found in six cases (10%); important interstitial inflammation was observed in 28 (44%). All patients received steroids with adjunctive immunosuppression in 54 cases (86%). After a median follow-up of 51 months (1–296), 58 patients (92%) were alive, nine (14%) were on chronic dialysis and two (3%) had undergone kidney transplantation. Conclusion: Necrotizing pauci-immune GN is the most common renal presentation in ANCA-positive EGPA. ANCA-negative patients had frequent atypical renal presentation with other glomerulopathies such as membranous nephropathy. An important eosinophilic interstitial infiltration was observed in almost 50% of cases.